2022
DOI: 10.1371/journal.pone.0274411
|View full text |Cite
|
Sign up to set email alerts
|

L-Arginine reverses maternal and pre-pubertal codeine exposure-induced sexual dysfunction via upregulation of androgen receptor gene and NO/cGMP signaling

Abstract: Background Although codeine has been reported to enhance sexual activity by improving penile reflexes, it has been shown to impair fertility indices. Also, codeine impairs ovarian steroidogenesis and folliculogenesis. Nonetheless, whether or not codeine exerts an epigenetic effect remains unclear. On the other hand, arginine has been speculated to enhance penile reflexes by upregulating NO/cGMP Signaling. Aim The study evaluated the effect of maternal codeine exposure and prepubertal codeine and arginine tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…It is credible to construe that codeine-induced alteration in testosterone levels and the decrease in AR may directly impair spermatogenesis ( 35 ). The present finding that codeine reduces testosterone levels aligns with previous reports that demonstrated that opioids such as tramadol and codeine lower testosterone level ( 14 , 17 , 18 , 26 , 44 ). Arginine supplementation blocked the codeine-induced decrease in testosterone and AR concentrations possibly by upregulating endocrine signaling pathways, especially the hypothalamic-pituitary-testicular axis evidenced by increased LH and FSH, which culminates in increased testosterone production and release, enhanced AR expression, and consequently improved spermatogenesis and sperm count.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…It is credible to construe that codeine-induced alteration in testosterone levels and the decrease in AR may directly impair spermatogenesis ( 35 ). The present finding that codeine reduces testosterone levels aligns with previous reports that demonstrated that opioids such as tramadol and codeine lower testosterone level ( 14 , 17 , 18 , 26 , 44 ). Arginine supplementation blocked the codeine-induced decrease in testosterone and AR concentrations possibly by upregulating endocrine signaling pathways, especially the hypothalamic-pituitary-testicular axis evidenced by increased LH and FSH, which culminates in increased testosterone production and release, enhanced AR expression, and consequently improved spermatogenesis and sperm count.…”
Section: Discussionsupporting
confidence: 93%
“…The administration was via gavage. The dose of codeine used is the submaximal peak dose obtained from the dose-response curve of our pilot study as previously reported ( 18 , 26 , 27 ) and that of arginine was as previously reported ( 28 ). Animals were culled at 12 weeks via euthanasia using intraperitoneal ketamine (4 mg/kg bw) and xylazine (40 mg/kg bw).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…A related study showed that arginine can treat endocrine disorders, delayed sexual maturity, and sexual dysfunction induced by codeine [37], and it can signi cantly increase the sperm density, total sperm count, and effective sperm count of the body [38,39]. Arginine is a precursor of nitric oxide (NO), which is an important signal and effector molecule in the body, plays an important role in the male reproductive system, and can promote vasodilation and penile smooth muscle relaxation.…”
Section: Effects Of Ascending and Descending Medicine On Kidneymentioning
confidence: 99%